An Analysis of Mathematical Self-Efficacy of the 10th Grade MIPA Students of MAN Salatiga - Ahmad Mukhibin; Wulan Izzatul Himmah (Universitas Tidar, 2020)
The skills required in the 21st century are highly varied. One of them is a skill in the affective aspect, such a self-efficacy which needs to be developed. Self-efficacy can affect someones future success. Someone who has a high self-efficacy will overshoot something easier than reality. But on the other hand, a person with low self-efficacy will perceive something more difficult than reality. This causes someone to get stress and depression easily. This research aims to find out and describe the mathematical self-efficacy of students. This research is qualitative descriptive research. The subjects of the research were the students of the 10th grade MIPA of MAN Salatiga for the academic year 2018/2019 which amounted to 73 students. The instrument is used as a self-efficacy questionnaire format developed from a self-efficacy of Sutanto (2018). The instrument consists of 20 statements and has been validated by expert lecturers. The results of the research showed that 2.74% of students have very low self-efficacy, 21.92% of students have a low self-efficacy, 57.53% of students have a high self-efficacy, and 17.81% of students have very high self-efficacy. This shows that mathematical self-efficacy of students need to be trained in order to be enhanced.